FUZZY INFERENCE SYSTEM MODEL IN MEASURING STUDENT SATISFACTION IN ACADEMIC SERVICES USING THE SUGENO METHOD - Sihaloho, Tulus Pramita; Wiguna, Dede Prabowo; Ginting, Sakaria Efrata (Sean Institute, 2022)
Analysis using a fuzzy approach is a solution to the problem of differences in the units of variables to be calculated correlation patterns. Almost all conventional analysis is approached with fuzzy methods. This results in calculations that are closer to the field situation. The Sugeno method is one of several methods in fuzzy analysis used in this study. Satisfaction is a situation where consumers are positive about a service or producer (service/product provider), in economics to find out this, several studies have been conducted. However, in the study, calculations were carried out using a firm set (crisp). While in this study, calculations were carried out using the Sugeno method. The results obtained in this study are the calculation of student satisfaction levels using the Sugeno method consists of several stages, namely: 1. Formation of fuzzy sets of product quality variables, 2. Formation of fuzzy rules that may occur where there are 42 rules, 3. Defuzzification (affirmation) using the weighted average calculation method which produces a defuzzification value of 67.47. Furthermore, research can be developed again using other parameters in determining the level of student loyalty until college graduation.